Psychometric Evidences of the Workaholism Battery in a Portuguese Sample - Santos, Joana; Sousa, Cátia; Sousa, António; Figueiredo, Luciano; Gonçalves, Gabriela (Journal of Tourism, Sustainability and Well-being, 2018)
Workaholism, defined as an addiction or dependence on work, is a subject that has become prominent in the literature, although its investigation is still at an early stage. The present study aims to adapt the Spence and Robbins’ Workaholism Battery - WorkBat (1992) to the Portuguese reality. The sample of the present study consists of 407 participants (313 women, 92 men, 2 don’t answered), aged between 18 and 68 years (M = 39; SD =10.449). The results from confirmatory analysis corroborate the original three factors structure: work involvement; work drive; work enjoyment. At the level of internal consistency, global and by dimension, the obtained values are acceptable; allowing reiterating what was observed in the original scale study. Although none of the models tested guarantees ideal adjustment values, either for the reasonableness of the values or for a better theoretical adequacy, the model considered more suitable meets the threefold solution initially proposed by Spence and Robbins (1992).